HAMLET, a human milk protein-lipid complex, modulates amoxicillin induced changes in an ex vivo biofilm model of the oral microbiome - Brar, Navdeep Kaur; Dhariwal, Achal; Shekhar, Sudhanshu; Junges, Roger; Hakansson, Anders P.; Petersen, Fernanda Cristina (Frontiers in Microbiology, 2024)
Challenges from infections caused by biofilms and antimicrobial resistance highlight the need for novel antimicrobials that work in conjunction with antibiotics and minimize resistance risk. In this study we investigated the composite effect of HAMLET (human alpha-lactalbumin made lethal to tumor cells), a human milk protein-lipid complex and amoxicillin on microbial ecology using an ex vivo oral biofilm model with pooled saliva samples. HAMLET was chosen due to its multi-targeted antimicrobial mechanism, together with its synergistic effect with antibiotics on single species pathogens, and low risk of resistance development. The combination of HAMLET and low concentrations of amoxicillin significantly reduced biofilm viability, while each of them alone had little or no impact. Using a whole metagenomics approach, we found that the combination promoted a remarkable shift in overall microbial composition compared to the untreated samples. A large proportion of the bacterial species in the combined treatment were Lactobacillus crispatus, a species with probiotic effects, whereas it was only detected in a minor fraction in untreated samples. Although resistome analysis indicated no major shifts on alpha-diversity, the results showed the presence of TEM beta-lactamase genes in low proportions in all treated samples but absence in untreated samples. Our study illustrates HAMLET's capability to alter the effects of amoxicillin on the oral microbiome and potentially favor the growth of selected probiotic bacteria when in combination. The findings extend previous knowledge on the combined effects of HAMLET and antibiotics against target pathogens to include potential modulatory effects on polymicrobial biofilms of human origin. Keywords: Antibiotic resistance, HAMLET, oral microbiome, oral resistome, amoxicillin, probiotics